THEORETICAL FOUNDATIONS OF ECONOMIC SYSTEM ACTIVITY AND FORECASTING IN THE CONDITIONS OF TRANSFORMATION PROCESSES (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2025)
This article presents ideas and considerations on the theoretical foundations of the functioning and forecasting of the economic system in the context of transformation processes.